A Hybrid PID-Fuzzy Control for Linear SISO Systems with Variant Communication Delays - Adrian-Bogdan Hanchevici; Monica Patrascu; Ioan Dumitrache (Advances in Fuzzy Systems)
We propose one networked control strategy for linear SISO systems affected by variant communication delays. The purpose of this approach is to adjust, by using the fuzzy logic, the command provided by the PID controller. The input for the fuzzy logic controller (FLC) is represented by the delay and the variation of delay, and the output is used to adapt the PID controller’s command to the new value of the communication delay which occurs in the network. Simulation and implementation results are presented. The results show performance improvement when using our control strategy. The authors present the implementation for an axis of a 3D crane, using the Ethernet/IP (TCP/IP) communication protocol.